A review of the Mexican national innovation system - Samantha Rullán; Lourdes Casanova (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Governments and business leaders are increasingly aware of the role that innovation plays in economic growth, development and competitiveness. There are imperative challenges for Latin American countries, among them, poverty, social inclusion, sustainable development, climate change, natural disasters, productivity, improve the quality of education and health. Innovations are essential to drive economic growth and prosperity in the region. According to the Global Innovation Index (2015), Mexico is ranked 57th. Most of the research on innovation performance is mostly focused on technological innovation. Therefore, the main variables used, such as patents and number of scientific publications, do not always reflect the other types of innovations (i.e. business model, organizational, etc.) that are developing in emerging markets. The aim of this paper is to analyze the Mexican innovation system using a broad concept with a focus on other types of innovation including cultural aspects to identify the main characteristics that distinguish and determine how innovation in Mexico is formed. Although the Mexican government has improved its institutional structure for innovation and its support policies, they need to evaluate programs and adjust incentive schemes based on performance to improve their innovation policy. Purpose - The purpose of this paper is to examine the Mexican National Innovation System using a broad concept with a focus on other types of innovation and including cultural aspects to identify some of the main characteristics that determine how innovation in Mexico is formed. Design/methodology/approach - The national innovation systems framework is used to review the Mexican innovation policy.A review of relevant literature on national innovation systems and Mexican innovation policies with data from the Global Innovation Index and INEGI were used for this paper. Findings - Higher private investment in R&D is needed to enhance innovation, the Mexican government needs to incentivise the private sector investment and collaboration with higher education institutions on innovation projects is essential. Mexico has improved its institutional structure for innovation and its support policies.An explicit innovation policy is recent and it is difficult to evaluate its effectiveness. Research limitations/implications - This study contributes to the debate on how to improve the Mexican innovation system with emphasis on a broad concept of innovation.The Mexican innovation data is limited. Originality/value - This paper provides a landscape from which policy makers and academics can build on to present proposals for ways to improve innovation performance in Mexico and other Latin American countries.
Keywords: O54; O29; 330; Innovation; Mexico; Innovation Policy; National Innovation System